PELAKSANAAN PERATURAN DAERAH KOTA DENPASAR NOMOR 24 TAHUN 2001 TENTANG USAHA HOTEL MELATI DI KOTA DENPASAR - I Putu Rudi Darmika; Ibrahim R.; I Nengah Suharta (Kertha Negara : Journal Ilmu Hukum, 2014)
Implementation of tourism accommodation activities pertaining to non-star hotelbusiness at first have been regulated by office of tourism Denpasar city, but as the emergence ofoffice of licensing, and occurring transition to the monitoring task of non-star hotel business.Where all the implementation of and supervision over non-star hotel business now governed byoffice of licensing local regulations number of 24/2001 on non-star hotel business. It is causingthe occurrence of problem where there are many non-starhotel business who commits anoffense against business permit such as : many non-star hotel business who no license, andmany non-star hotel business which is not extend the license, and many non-star hotel businessthat has changed ownership, but not registered it and there is also a non-star hotel businesswhich have previously been registered in tourism agency, but after it has occurred transition theeffort is not registered back. This article uses empirical legal research. From the descriptionabove then can be concluded that the implementation of and supervision over non-star hotelbusiness in the city of denpasar still not fit with local regulation number of 24 / 2001 on nonstarbusiness.